IDENTIFIKASI JENIS BUNGA MENGGUNAKAN EKSTRAKSI CIRI ORDE SATU DAN ALGORITMA MULTI SUPPORT-VECTOR MACHINES (MULTISVM) - Teuku Reza Pahlefi; Relita Buaton; Nurhayati Nurhayati (Jurnal Informatika Kaputama (JIK), 2021)
Flowers are a means of generative reproduction of closed seed plants. In the flower sections there are various or also types of parts in the flower, each of which has different functions in each part of the flower, so that a long and broad discussion is needed regarding the parts of the flower on a daily basis. day is also used to refer to a structure which is botanically known as compound interest or inflorescence. Compound interest is a collection of flowers collected in one bouquet. In this context, the unit of interest that makes up compound interest is called a floret. Flower is actually a modification of the leaves and stems to support a closed fertilization system. The fertilization system is closed, namely because the ovule is protected in the ovary or ovary and this is also another characteristic. The purpose of this study was to classify 12 Banten batik motifs using the SVM method. The research was carried out in several stages, namely resizing to equalize the dimensions of the image, grayscale to simplify the image by converting it to a gray level image, median filter to remove noise in batik, and feature extraction as input for classification using SVM. The classification results using SVM order 1 is 85%, and for order 2 is 87.2.